Benchmarking newborn care quality in Ghana: Evidence from structured observations of clinical practice against WHO quality standards - Solomon Mohammed Salia; Billie de Haas; Jelle Stekelenburg; Robert Kaba Alhassan (PLoS ONE, 2026)
Introduction The neonatal mortality rate in Ghana remains above the global average, which is far from meeting SDG 3.2. Notably, institutional neonatal deaths are on the increase, potentially due to healthcare professionals’ poor adherence to quality newborn care guidelines. This study assessed the adherence of clinical healthcare professionals to guidelines on quality newborn care in Ghana. Methods This observational study collected data from 158 healthcare professionals across six health facilities in Ghana. A data collection tool was developed based on the WHO standard for improving quality of care for small and sick newborns and the Ghana Health Services Standards for Newborn Health Services . The Mann-Whitney U test was used to measure differences in categorical data, while logistic regression models were employed to analyse the association between dependent and independent variables at a 95% confidence level. Six facility-level discussions with the observed healthcare professionals were held to validate and interpret the quantitative findings. Results Overall, only 31 (20%) of healthcare professionals demonstrated good adherence to infection prevention and control (IPC), while 73 (46%) adhered poorly. Moderate adherence levels were seen in essential care for every newborn (ECEN) at 53% and respectful maternal and newborn care at 51%. During validation discussions, healthcare professionals mentioned poorly located handwashing materials, parental preference for methylated spirit over chlorhexidine for umbilical cord care, and lack of protocols for pain assessment as key barriers to adherence. Conclusion The study findings revealed low adherence levels to quality newborn care practices, especially in IPC practices. Moderate adherence levels were found in ECEN and respectful maternal and newborn care. These findings highlight the need to improve adherence with quality newborn care standards in Ghana. The Institutional Care and Family Health Divisions of the Ghana Health Service should integrate these findings into ongoing quality improvement efforts to achieve better neonatal outcomes.